Improved transparency and hardness in α-alumina ceramics fabricated by high-pressure SPS of nanopowders. Issue 1 (January 2017) - Ghanizadeh, Shaghayegh; Grasso, Salvatore; Ramanujam, Prabhu; Vaidhyanathan, Bala; Binner, Jon; Brown, Peter; Goldwasser, Judah
Abstract: Nanocrystalline alumina powder with an average crystallite size of ≤50 nm has been consolidated by spark plasma sintering (SPS) and hot pressing (HP) with a view to achieving dense, fine grained alumina bodies that display transparency. When as-synthesised powder was densified directly, excessive grain growth resulted from both the SPS and HP techniques and hence a large final grain size was observed. Attempts to improve the uniformity of the green microstructure prior to densification were unsuccessful when spray freeze dried granules were used, whether pre-pressed into a compact or not. The use of 53% dense slip cast green compacts, however, enabled final density of ~99.96% and a mean grain size of ~0.32 µm to be achieved when SPS conditions of 1200 °C and 500 MPa were applied for 20 min. These samples offered in-line transmittance values of up to ~80% and microhardness values of 22 GPa.